2021
DOI: 10.3390/genes12020240
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Genetic Variation in MHC-Linked Microsatellite Markers from Native Chicken Breeds

Abstract: The major histocompatibility complex (MHC) is a highly polymorphic gene region that regulates cellular communication in all specific immune responses. In this study, we investigated 11 microsatellite (MS) markers in the MHC-B region of chicken populations from four countries: Sri Lanka, Bangladesh, South Korea, and Nigeria. The MS markers were divided into two sets. Set 1 included five novel MS markers, which we assessed using 192 samples from 21 populations. Set 2 included six previously reported markers, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
10
2
Order By: Relevance
“…Compared to the present result very low genetic identity was reported between White Leghorn and KNC white of Korea as well as Ghagus and Nicobari Haunshi et al, 2020;Manjula et al, 2021). The Nei's original measure of genetic distance between Tellicherry and broiler was estimated to be 0.1958 and Nei's unbiased measure of genetic distance to be 0.1718.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…Compared to the present result very low genetic identity was reported between White Leghorn and KNC white of Korea as well as Ghagus and Nicobari Haunshi et al, 2020;Manjula et al, 2021). The Nei's original measure of genetic distance between Tellicherry and broiler was estimated to be 0.1958 and Nei's unbiased measure of genetic distance to be 0.1718.…”
Section: Resultscontrasting
confidence: 96%
“…The Nei's original measure of genetic distance between Tellicherry and broiler was estimated to be 0.1958 and Nei's unbiased measure of genetic distance to be 0.1718. Compared to this result very high genetic distance was reported between White Leghorn and KNC white of Korea as well as Ghagus and Nicobari (Thakur et al, 2017;Haunshi et al, 2020;Manjula et al, 2021). At the same time based on polymorphism analysis with SNP chip data close relationship with Korean KNC with Rhode Island Red and Cornish was revealed (Manjula et al, 2021).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The range of the LEI0258 allele in this study was 193-509 bp. This is different from the study of Manjula et al [15] identified 38 LEI0258 allele range of 193-539 bp. In Chinese indigenous chicken strains, 69 alleles were identified, ranging from 193-489 bp [16], 26 alleles in North American and European layer-type chickens [9], and 22 alleles in 2 commercial layer and five non-commercial layer chickens, range 182 to 552 bp [8].…”
Section: Discussioncontrasting
confidence: 97%
“…In addition to LEI0258, there are also many microsatellite loci such as MCW0370 and MCW0371. The use of these high polymorphism markers is of great significance for the study of chicken MHC diversity (Esmailnejad et al, 2017;Manjula et al, 2021).…”
Section: Introductionmentioning
confidence: 99%